Varicocele and testicular cord torsion: immune testicular microenvironment imbalance - Guazzone, Vanesa A.; Lustig, Livia (Frontiers in Cell and Developmental Biology, 2023)
The main functions of the testis, steroidogenesis and spermatogenesis, depend on the endocrine axis and systemic and local tolerance mechanisms. Infectious or non-infectious diseases may disturb testicular immune regulation causing infertility. Literature has illustrated that bacterial and viral infections lead to autoimmune infertility: either sperm antibodies or autoimmune epidydimo-orchitis. However, little is known about the association between non-infectious testicular pathologic diseases and autoimmunity. Here we review the novel aspect of varicocele and testicular cord torsion pathology linked to inflammation and discuss how immune factors could contribute to or modulate autoimmunity in ipsi-and contralateral testis.